The Comparison of Cultural Equivalence in Indonesian and German Versions of Show Yourself Songs - Nareswari, Vianey Somya; Rosyidah, Rosyidah (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
This study aims to describe the comparison of cultural aspect equivalence in the Indonesian and German translated versions of the song Show Yourself. In this research, a qualitative method is used with datasources in the form of the original song lyrics entitled‘Show Yourself’, the lyrics of the Indonesian translated version entitled Tunjukkan dirimu, and the lyrics of the German translated version entitled Zeige Dich. Meanwhile, the data of this research are words, phrases, clauses, and sentences that are culturally charged in the lyrics of these songs. The technique of ‘Simak Catat’ is an activity of listening and recording existing information from data sources to obtain data. After that, it was analyzed with three stages, namely data reduction, data presentation, and conclusion drawing/verification. The results showed that there are four of the five categories of linguistic forms of cultural aspects proposed by Stolze in the song, namely the concept of terminology, language form, syntax, and pragmatics. In addition, according to Pym's equivalence theory, both translated versions of the song use the concept of directional equivalence, i.e. the translator uses a free strategy in the process of translating the song.